Characterisation analysis of national greenhouse gas emissions in DPR of Korea: emission trends for a 12-year period. (21st May 2019) - O, Nam-Chol; Kim, Hun; Kim, Gi-Sun; Ri, Gum-Su
DPR of Korea ratified the United Nations Framework Convention on Climate Change (UNFCCC) on 5 December 1994, the Kyoto Protocol on 27 April 2005 and the Paris Agreement on 1 August 2016. As a party of the convention on climate change, DPR of Korea submitted the national greenhouse gas (GHG) emissions inventories to the UNFCCC secretariat, respectively. This study aimed at analysing the characterisation of national GHG emissions in DPR of Korea for a 12-year period (1990-2002), conducted according to 2006 IPCC guidelines. The results show that DPR of Korea accounted for 0.5% of the world GHG emissions in 1990, but only 0.2% of the emissions in 2002. The amount of cumulative GHG emissions was approximately 1, 503, 820 Gg CO2 e (CO2 equivalent) in the period 1990-2002, which accounted for 0.3% of the world cumulative GHG emissions. This showed that DPR of Korea definitely contributed to global warming, although the emissions were negligible, compared to the world emissions.